HEAVY METALS REMOVAL USING SUGARCANE BAGASSE DERIVED ACTIVATED CARBON IN PHYSICAL AND BIOLOGICAL TREATMENT SYSTEMS. - SALIHI, IBRAHIM UMAR (2017)
Wastewater is essentially the water supply of the community after it has been used in a variety of applications that contains constituents which render it unsuitable for most use without treatment. Domestic effluents are one of the main sources of wastewater that contained contaminants which can be harmful to human, plants and animals. The major contaminants of concern are the heavy metals. Heavy metals contamination has been an issue to the environment and human health. The persisting contamination level has been observed and concerned by the public due to continuous deterioration. Biological wastewater treatment is the main techniques used for the treatment domestic wastewater. Batch adsorption technique is normally employed to treat wastewater containing heavy metal using activated carbon. This study focused on the development of activated carbon from sugarcane bagasse to reduce toxic effect of Cu2+, Zn2+, Cd2+ and Pb2+, on activated sludge microorganisms treating domestic wastewater. The selected metals are mainly present in domestic sewage nowadays. The study consisted of three phases; (1) adsorbent preparation in its optimum conditions using response surface method; (2) batch adsorption study in order to investigate the adsorption capacities of the produced adsorbent as well as the raw sugarcane bagasse for the removal of heavy metals; and (3) continuous flow treatability study of domestic wastewater impacted with heavy metals using the produced adsorbent under different heavy metals. The produced adsorbent have high surface area of 599 m2/g, under heating rate of 10 °C/min, residence time of 3 hours and temperature of 900 °C, respectively. The produced adsorbent have higher adsorption capacities of 38.4 mg/g, 21.05 mg/g, 19.37 mg/g and 23.4 mg/g compared to the raw sugarcane bagasse having adsorption capacities of 9.37 mg/g, 13.4 mg/g, 10.51 mg/g and 3.93mg/g, for heavy metals of Cu2+, Zn2+, Cd2+ and Pb2+, respectively. The produced adsorbent was able to delay the toxic effect of Cu2+, Zn2+, Cd2+ and Pb2+ on the activated sludge microorganisms treating domestic wastewater provided that their toxicity does not exceed 4.10 mg/L, 3.12 mg/L, 6.20 mg/L and 1.5 mg/L for Cu2+, Zn2+, Cd2+ and Pb2+, respectively.